Faculty Senate Internationalization and Globalization Committee Meeting Minutes, October 20, 2021 - Valdosta State University, Internationalization and Globalization Committee (Valdosta State University Archives and Special Collections, 2021)
Valdosta State University Faculty Senate Internationalization and Globalization Committee Meeting Minutes, October 20, 2021. Electronic records. 1 PDF document.
1 electronic records and derivatives. PDF. 61421 bytes.
Keywords: Electronic records; Minutes (Records); Valdosta State University. Faculty Senate. Internationalization and Globalization Committee